2008
DOI: 10.1007/s10495-008-0246-1
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid induces apoptosis in lung cancer cells by increasing MKP-1 and down-regulating p-ERK1/2 and p-p38 expression

Abstract: Different agents able to modulate apoptosis have been shown to modify the expression of the MAP-kinase-phosphatase-1 (MKP-1). The expression of this phosphatase has been considered a potential positive prognostic factor in lung cancer, and smoke was shown to reduce the levels of MKP-1 in ferret lung. Our aim was to assess whether the n-3 polyunsaturated fatty acid docosahexaenoic acid (DHA), known to inhibit the growth of several cancer cells mainly inducing apoptosis, may exert pro-apoptotic effect in lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 65 publications
(101 reference statements)
6
45
0
3
Order By: Relevance
“…Increased consumption of omega-3 FAs has been associated with a lower incidence of various types of cancer, including colon (2), breast (3,4) and prostate cancer (3,4). It has also been demonstrated that omega-3 FAs exert a range of anti-tumor effects, including inhibitory effects on angiogenic mediator production (5), the induction of apoptosis (6), inhibitory effects on tumor invasion and metastasis (7,8) and regulatory effects on signaling pathways (9). In particular, the anti-tumor effects of EPA and DHA have been observed in breast cancer, whereby higher intakes of these FAs are associated with a reduced risk of mortality (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased consumption of omega-3 FAs has been associated with a lower incidence of various types of cancer, including colon (2), breast (3,4) and prostate cancer (3,4). It has also been demonstrated that omega-3 FAs exert a range of anti-tumor effects, including inhibitory effects on angiogenic mediator production (5), the induction of apoptosis (6), inhibitory effects on tumor invasion and metastasis (7,8) and regulatory effects on signaling pathways (9). In particular, the anti-tumor effects of EPA and DHA have been observed in breast cancer, whereby higher intakes of these FAs are associated with a reduced risk of mortality (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Cells at a density of 2x10 6 were treated with 0 (control), 50 and 100 µM DHA for 6 h, then lysed in radioimmunoprecipitation assay buffer composed of 10 mM tris-HCl (Nacalai Tesque, Inc., Kyoto, Japan), 150 mM NaCl (Kanto Chemical, Co., Inc., Tokyo, Japan), 1% Triton X-100 (MP Biomedicals LLC, Santa Ana, CA, USA), 5 µM ethylenediaminetetra acetic acid (Nacalai Tesque, Inc.), 1%sodium deoxycholate (Difco; BD Biosciences, San Jose, CA, USA), 0.1% sodium dodecyl sulfate, 1.2% aprotinin, 5 µM leupeptin, 4 µM antipain, 1 mM phenylmethylsulfonyl fluoride and 0.1 mM Na 3 VO 4 (all; Sigma Aldrich; Merck KGaA, Darmstadt, Germany) according to a previously described method (21). Samples were centrifuged at 16,000 x g for 20 min at 4˚C.…”
Section: Introductionmentioning
confidence: 99%
“…or p38 MAPK pathways being a negative regulator of ERK1/2, JNK or p38 MAPK , respectively. DUSP1 may induce apoptosis (27)(28)(29)(30). Following exposure to stress agents various degrees of histone H3 modification at the DUSP1 chromatin occurs.…”
Section: Time-resolved Expression Profile Of Upregulated Genes (Fig mentioning
confidence: 99%
“…Jego działanie proapoptotyczne wynika m.in. z hamowania ekspresji enzymu cyklooksygenazy 2 (COX-2), powodującego wzrost guza oraz neoangiogenezę [15]. W badaniach Serini i wsp.…”
unclassified
“…W badaniach Serini i wsp. [15] przeprowadzonych na liniach komórkowych: A549 -ludzkiego gruczolakoraka płuc, BEN -ludzkiego raka nabłonka płaskiego płuc, a także na linii komórek zwierzęcych Mv1Lu zaobserwowano indukcję apoptozy podczas 48-godzinnej inkubacji z DHA we wszystkich trzech liniach komórkowych. Stwierdzono, że 50-mikromolowy roztwór DHA spowodował ekspresję białka fosfatazy 1 dla kinazy białkowej aktywowanej mitogennie (MKP-1) w badanych liniach komórkowych.…”
unclassified